Media Representasi Tentang Kesiapsiagaan Bencana di Kawasan Wisata Pantai Pangandaran - Khaerani, Rijal; Hartadji, Diandra Khansa; Winarsih, Gladis Dwi; Dianada Jayati, Jeanita Einsteinovi; Krista, Sellin Alifia; Gitasiswhara, Gitasiswhara; Khosihan, Aan (Manajemen dan Pariwisata, 2024)
This research examines disaster preparedness in the tourist area of Pangandaran Beach, West Java. Pangandaran Beach is a popular tourist attraction and is located in an area vulnerable to natural disasters such as earthquakes and tsunamis. In the face of potential disaster risks and threats, preparedness becomes very important to protect tourists and local communities. However, awareness about preparedness is not always well implemented. This research focuses on the preparedness of tourism stakeholders such as the government, businesses, and tourists in the area. In addition, this research also highlights the role of media representation in conveying information about disaster preparedness, including the potential impact of untrue news or hoaxes. Qualitative methods and "Critical Media Discourse Analysis" are used to reveal the views and experiences of the parties related to disaster preparedness in Pangandaran Beach. The results of this research are expected to contribute to improving preparedness and risk mitigation efforts in the tourist area.